Mediterranean island endemic Arum pictum emits isomyocorene as a major component of floral scent - Gibernau, Marc; Amadori, Arianna; Godschalx, Adrienne; Albre, Jérôme; Tomi, Félix; Marcia, Paolo; Farris, Emmanuele (Comptes Rendus. Chimie)
The west Mediterranean Arum pictum L.f., endemic from Corsica, Sardinia and Balearic Islands, is the only autumn-flowering Arum species. This species is pollinated by deceptively attracting coprophilous and saprophilous Diptera and staphylinid Coleoptera. Four populations from Sardinia and Corsica were studied. The inflorescence produces heat during anthesis from the appendix and stamens; the appendix is able to increase its temperature twice within the same day, a trait unique in Arum. A. pictum floral scents likely mimic horse/donkey dung by releasing several dung-related volatile organic compounds (VOCs: $p$-cresol, skatole, or indole). Surprisingly, the main floral VOC was 2,6-dimethylocta-1,3,7-triene or isomyocorene.